Sisterhood in sports : how female athletes collaborate and compete - Steidinger, Joan (Rowman and Littlefield, 2014)
"Sisterhood in Sports: How Female Athletes Collaborate and Compete tells the stories of all kinds of female athletes in a variety of sports. Their natural tendency to use talking as a primary form of communication is essential to their experiences and successes in sports. Women and girls tend to have BFFs, collaborate during periods of stress, express empathy for one another, worry about themselves and others, and desire to have fun in sports, which makes their experiences of sports and competition different from those of their male counterparts. Female strengths are grounded in both mind and body, and they take these strengths onto the court, field, and track."--Back cover